2015
DOI: 10.5301/ejo.5000590
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Aspects and Depression in Patients with Retinitis Pigmentosa

Abstract: Patients with RP seem to present mild to moderate depressive symptoms in comparison with healthy control subjects without visual impairment. These symptoms were found to be correlated with BCVA and age, suggesting that visual loss and older age in patients with RP could be predictive factors of their emotional status. Therefore, there is need for close monitoring and supportive management of this population, so as to detect depression and to treat it promptly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
2
21
0
1
Order By: Relevance
“…It is important to note that the depressive state was found to be significantly associated with every aspect of visual function including the BCVA in the better or worse eye, and the FAS, FFS, FVS and the NEI-VFQ25 subscale score. These significant correlations were also found in other studies [ 12 15 ]. Thus, Hahm et al found a significant relationship between visual functions and a depressive state in RP patients, however it was not found in such visual functional tests as the weighted visual acuity score or FVS [ 12 ].…”
Section: Discussionsupporting
confidence: 89%
“…It is important to note that the depressive state was found to be significantly associated with every aspect of visual function including the BCVA in the better or worse eye, and the FAS, FFS, FVS and the NEI-VFQ25 subscale score. These significant correlations were also found in other studies [ 12 15 ]. Thus, Hahm et al found a significant relationship between visual functions and a depressive state in RP patients, however it was not found in such visual functional tests as the weighted visual acuity score or FVS [ 12 ].…”
Section: Discussionsupporting
confidence: 89%
“…This study did not record whether participants were seeking treatment from a health professional or taking any medication at the time of the study. This may have altered the results if it had been taken into account as previous research has stated that treatments and therapies impact VRQoL [ 2 , 7 , 9 ]. Thus, future research aimed at a general community population should initially record treatment status and, if it is a longitudinal design, monitor any changes in treatment status.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a relationship between emotional health and coping strategies, where engaging or disengaging coping strategies may indicate emotional health levels. Being diagnosed with RP is associated with developing depressive symptoms, poor mental wellbeing, and lower levels of general happiness with life [ 7 ]. Therefore, coping strategies and emotional health seems to be highly associated with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the aforementioned association, detecting depression in patients with age-related macular degeneration [ 25 ], glaucoma [ 28 ], retinitis pigmentosa [ 29 ], and Stargardt disease [ 30 ]. As for the KC, studies demonstrated controversial conclusions.…”
Section: Introductionmentioning
confidence: 99%